'They need to ask me first'. Community engagement with low‐income citizens. A realist qualitative case‐study - Esther De Weger; Caroline Baan; Cheryl Bos; Katrien Luijkx; Hanneke Drewes (Wiley, 2022)
Abstract Background Community engagement is seen as key to citizen‐centred and sustainable healthcare systems as involving citizens in the designing, implementation and improvement of services and policies is thought to tailor these more closely to communities' own needs and experiences. Organizations have struggled to reach out to and involve disadvantaged citizens. This paper examines how if, why, and when low‐income citizens wish to be involved. Methods For this qualitative realist case‐study, 19 interviews (one dyad) were held with (20) low‐income citizens in two Dutch municipalities. Additionally, the results were discussed with a reference panel consisting of professionals and citizens to enrich the results and to ensure the results had face validity. Results The results showed four different ways in which low‐income citizens wished to be involved: (a) in a practical/volunteer way; (b) as a buddy; (c) as a lay expert; (d) not involved at all. The factors affecting citizens' interest and capacity to participate include citizens' own experiences of the services they access and their personal situations, e.g. their mental or physical health, extent of financial crisis, family situation, home environment. None of the interviewees was currently involved, but all had ideas for improving health(care) services and policies. Citizens' experiences of the services they accessed acted as a motivator for some to be involved as they wanted to ensure others would not have the same struggles, while for others their own needs and an apathetic system remained too high a barrier. To enable involvement, citizens need continued support for their own health(care) and financial situation, better communication and accessibility from services, practical support (e.g., training and bus passes) and recognition for their input (e.g., monetary compensation). Conclusion The study shows that citizens' experiences of the services they accessed influenced if and how they wanted to be involved with health and care services. Despite the fact that all participants had shared solid ideas for improving services and policies, they were hindered by a bureaucratic, impersonal and inaccessible system. Organizations seem to underestimate the required investments to reach out to low‐income citizens and the support required to ensure their involvement. Patient and Public Involvement (PPI) in Study Citizens as well as PPI organizations were members of the reference panel who helped formulate the research questions and recruitment strategy. The local reference panel also helped to interpret and refine the initial findings.